Precise measurement of hyperfine structure in the 3S1/2 state of 7Li - Pushpander Kumar (Nature Portfolio, 2017)
Abstract We report a precise measurement of hyperfine structure in the 3S1/2 state of the odd isotope of Li, namely 7Li. The state is excited from the ground 2S1/2 state (which has the same parity) using two single-photon transitions via the intermediate 2P3/2 state. The value of the hyperfine constant we measure is A = 93.095(52) MHz, which resolves two discrepant values reported in the literature measured using other techniques. Our value is also consistent with theoretical calculations.